(untitled) (Aporte Santiaguino, 2020)
The purpose of this studywas to describe some indicators that favor or hinder the scientific production of higher education teachers from two universities in Lima.With a descriptive design, it seeks to identify the main indicators that intervene in this problem. The participants were 33 teachers, who have a specific relationship with researchers and / or teach methodology courses, a thesis seminar, etc. The instrument used was the questionnaire on attitude, knowledge and Use of resources for research (ACRIN), which consists of 30 items divided into three factors: attitudes towards research, knowledge about research and use of resources for research. The results show that some of the factors for which university professors do not carry out research are mainly related to the lack of resources they receive, the lack of attitude they present and the low level of knowledge about research.We conclude, therefore, that the lack of scientific production in our environment is due mainly to the lack of resources available to teachers to do research.